A narrative review on the physicochemical profiles, bioactive compounds, and therapeutic potentials of stingless bee honey - Nor Liyana, Ja’afar; Nurfaizatul Aisyah, Ab Aziz; Zaida, Zakaria; Muzaimi, Mustapha; Mahaneem, Mohamed; Mohd Zulkifli, Mustafa; Sabarisah, Hashim (Springer Nature, 2025)
Stingless bee honey (SBH) is an intriguing type of honey produced by various genera of stingless bees. SBH has traditionally been used for its reputed therapeutic properties; yet scientific exploration on this honey remained less widespread compared to other types. This review aims to report recent physiochemical and phytochemical properties of SBH across various species and geographical origins. This review also aims to delve into the therapeutic potential of SBH, with a specific focus on its antioxidant, antibacterial, anticancer, and antidiabetic properties. By examining various studies on the medicinal attributes of SBH, this paper offers compelling evidence of its efficacy in treating diverse conditions, such as infections, inflammation, and many more. Furthermore, the distinctive composition of SBH was explored in detail, shedding light on its contribution to its remarkable medicinal characteristics. Ultimately, this review underscores the promising therapeutic potential of SBH and advocates further research to comprehensively comprehend its medicinal properties and unlock its potential for various medical applications.